Immigrants, imports, and welfare: Evidence from household purchase data - Brett A. McCully; Torsten Jaccard; Christoph Albert (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
Do immigrants make goods from their origin country more accessible to their non-immigrant neighbors? We augment U.S. grocery scanner data to include the origin country of both households and products, thereby enabling the first direct estimate of how local immigrant presence affects import penetration. Using a quantitative model of trade, we show that immigrants increase the grocery import expenditure share by 8%. Three quarters of this effect is attributable to immigrants' own disproportionate preferences for imported goods. Immigrants therefore raise import expenditures primarily through their own consumption, with muted benefits for their non-immigrant neighbors. The benefits that do accrue to natives are concentrated within high-income and urban households.
Keywords: F22; J31; J61; R11; 330; Import demand; immigrant preferences; household heterogeneity; spillover effects